2021
DOI: 10.1038/s41598-021-86443-4
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism is a long-term cognitively challenging experience that modulates metabolite concentrations in the healthy brain

Abstract: Cognitively demanding experiences, including complex skill acquisition and processing, have been shown to induce brain adaptations, at least at the macroscopic level, e.g. on brain volume and/or functional connectivity. However, the neurobiological bases of these adaptations, including at the cellular level, are unclear and understudied. Here we use bilingualism as a case study to investigate the metabolic correlates of experience-based brain adaptations. We employ Magnetic Resonance Spectroscopy to measure me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…This was accompanied by a collection of detailed language background information permitting quantification of bilingual experience on an individual level along a spectrum. We treat language experience and regress it as a dynamic, continuous variable within a collapsed group of all participants (functional monolinguals and bilinguals) and then only within the self-identifying bilingual sample, as in Pliatsikas et al (2021). In this way and in line with calls in the recent literature (Luk and Bialystok 2013;DeLuca et al 2020;de Bruin 2019), we sidestep two potential comparative fallacies: (a) the assumption that monolinguals and bilinguals form a priori distinct groups and (b) that the members of either group are so similar to one another in relevant sense that that individual variation is trivial.…”
Section: The Present Studymentioning
confidence: 99%
“…This was accompanied by a collection of detailed language background information permitting quantification of bilingual experience on an individual level along a spectrum. We treat language experience and regress it as a dynamic, continuous variable within a collapsed group of all participants (functional monolinguals and bilinguals) and then only within the self-identifying bilingual sample, as in Pliatsikas et al (2021). In this way and in line with calls in the recent literature (Luk and Bialystok 2013;DeLuca et al 2020;de Bruin 2019), we sidestep two potential comparative fallacies: (a) the assumption that monolinguals and bilinguals form a priori distinct groups and (b) that the members of either group are so similar to one another in relevant sense that that individual variation is trivial.…”
Section: The Present Studymentioning
confidence: 99%
“…However, such a view is not supported by other studies which show a broad variability in habitual code-switching patterns across bilingual communities (Backus, 2005;Lai & O'Brien, 2020). Korenar et al (2021) followed up on DeLuca et al ( 2019) but they additionally tested their hypotheses that the effects of bilingualism on the brain may be nonlinear (Pliatsikas, 2020) by using Generalised Additive Models (GAMs) for modelling possible non-linear brain adaptations (Pliatsikas, 2021;Pliatsikas et al, 2020). The study showed that volumes of the thalamus related linearly, and volumes of the caudate nucleus related non-linearly to the degree of bilingual experiences as measured using a composite score derived from the LSBQ, which subsumes information about code-switching frequency.…”
Section: Bilingualism-induced Structural Brain Changes In the Thalamu...mentioning
confidence: 98%
“…However, questionnaires that evaluate participants' language experience and language use focus on bilinguals, neglecting the different and specific linguistic experiences of monolinguals. Participants categorized as monolinguals are either not asked to fill out more detailed questions about their language experience, or the information on their linguistic experiences is gathered using bilingual questionnaires (e.g., [35]). In both cases, the linguistic diversity of a monolingual environment (e.g., (in)formal language learning and passive exposure to other languages, or sporadic active use of foreign languages) tends to be overlooked.…”
Section: Assessing Language Experience In Bilinguals and Monolingualsmentioning
confidence: 99%
“…While some researchers have used bilingual questionnaires to categorize participants as monolinguals or bilinguals (e.g., LEAP-Q for [45,46]) or to position them on a continuum (e.g., LSBQ for [35,[47][48][49][50]), we propose that monolinguals should complete different questionnaires than their bilingual peers, and these questionnaires should include questions that are relevant to capture their specific linguistic experiences. For example, the LSBQ [31] contains a detailed assessment of language use; nevertheless, it instructs participants to include languages that they can "speak and understand".…”
Section: Insights For Future Researchmentioning
confidence: 99%